Preparation method of anisotropic conductive adhesive connection socket for chip testing
By using printing technology and negative pressure technology in the manufacturing of chip test connection sockets, uniform filling of conductive adhesives is achieved, and the problems of high cost and complex operations in the existing technology are solved, and performance and reliability are improved.
Patent Information
- Application Number
- CN202411257735.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The manufacturing technology of existing chip test connection sockets relies on high-cost magnetic forming equipment, and material selection limits performance improvements, high operating complexity, resulting in increased production costs and complexity.
Using a method combining printing technology and negative pressure technology, the uniform filling of conductive adhesive is achieved through optimizing the printing process and vacuum negative pressure control, and the dependence on magnetic forming equipment is reduced.
It significantly reduces production costs, improves the conductivity and signal transmission stability of the chip connection socket, avoids the short circuit problem caused by the random spread of metal particles in traditional technology, and ensures the performance and reliability of the connection socket.
Smart Images

Figure CN119132739B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chip testing, and in particular relates to a method for preparing an anisotropic conductive adhesive connection socket for chip testing. Background Art
[0002] In the semiconductor industry, connector sockets are key components that connect chips and test equipment and are essential to ensure chip performance evaluation. These connector sockets must be able to accurately align with the pins of semiconductor chips to achieve efficient and accurate signal transmission. The mainstream connector socket manufacturing technology on the market currently relies on a specific magnetic forming equipment. The basic process of this technology involves mixing metal particles with organic silicone and injecting them into a specific mold designed with a conductive channel. Under the action of the magnetic field, the metal particles will be redistributed along a predetermined path to form a conductive channel synchronized with the pins of the chip to be tested.
[0003] However, this technology has several significant drawbacks. First, the development cost of the magnetic forming equipment for this process is very high, which greatly increases the production cost of the connection socket. Secondly, this process has specific requirements for the magnetism of metal particles, and generally uses materials such as nickel and chromium. However, with the development of chip technology, the conductivity requirements for a single pin are getting higher and higher. The choice of this traditional material limits the improvement of product performance. In addition, the process requires high technical knowledge of the operator, and requires an in-depth understanding of electromagnetic knowledge and fluid knowledge. In addition, the electromagnetic force of each product needs to undergo multiple tests to meet the production application standards, which increases the complexity and cycle of production.
[0004] Therefore, it is necessary to provide a new solution to the above technical problems. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing an anisotropic conductive adhesive connection socket for chip testing, which has a simple preparation process, low production cost, and excellent performance of the prepared connection socket.
[0006] To achieve the above purpose, the technical solution provided by the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing an anisotropic conductive adhesive connection socket for chip testing, which comprises:
[0008] A substrate having a plurality of conductive through holes corresponding to the pins of a chip to be tested is provided, wherein the substrate comprises a laminated base material layer and an insulating elastic layer; the substrate is placed on an air guide plate of a printing device, so that the air guide holes on the air guide plate are aligned with the conductive through holes on the substrate; a vacuum support carrier and a stencil of the printing device are aligned in the up-down direction, and the air guide plate carrying the substrate is moved between the vacuum support carrier and the stencil, so that the air guide holes on the air guide plate are aligned with the air suction holes of the vacuum support carrier, and the conductive through holes of the substrate are aligned with the mesh holes of the stencil; the vacuum support carrier is bonded to the lower surface of the air guide plate, and the stencil is bonded to the upper surface of the substrate; the vacuum support carrier is connected to a negative pressure generator, and negative pressure is formed in the conductive through holes through the air suction holes and the air guide holes; Conductive glue is coated on the screen, and a scraper is used to reciprocate and print 24 to 30 times, so that the conductive glue is filled into the conductive through-hole under the pressure of the scraper and the negative pressure; during the printing process, the vacuum pressure of the negative pressure generator is first gradually increased to a first pressure, and after being maintained at the first pressure for a predetermined time, it is gradually increased to a second pressure, and maintained at the second pressure until the printing is completed; the scraper maintains the first pressure during the first 6 to 8 printings, the scraper maintains the second pressure during the middle 8 to 10 printings, and the scraper maintains the third pressure during the last 10 to 12 printings, and the first pressure is greater than the second pressure and greater than the third pressure; the substrate filled with conductive glue after printing is thermally cured to solidify the conductive glue in the conductive through-hole to obtain a chip connection socket.
[0009] In one or more embodiments, the scraper has a single printing time of 8 to 10 seconds and a single printing displacement of 180 to 200 mm.
[0010] In one or more embodiments, during the printing process, the vacuum pressure of the negative pressure generator gradually increases to 0.06-0.08 MPa within 48-60 seconds, maintains at 0.06-0.08 MPa for 112-140 seconds, and then gradually increases to 0.09-0.11 MPa within 24-30 seconds, and maintains at 0.09-0.11 MPa until printing is completed.
[0011] In one or more embodiments, the pressure of the scraper is 55-65N during the first 6-8 printings, 35-45N during the middle 8-10 printings, and 25-35N during the last 10-12 printings.
[0012] In one or more embodiments, the conductive adhesive comprises the following raw materials, in parts by mass:
[0013] 80-90 parts of organic silicon resin with a molecular weight of 30-50, 10-20 parts of organic silicon oil, 0.5-1 part of inhibitor, 5-10 parts of hydrogen-containing silicone oil, 0.5-1 part of platinum catalyst, and 500-700 parts of non-magnetic conductive particles.
[0014] In one or more embodiments, the silicone resin is HSV-1510 produced by Jiangxi Riyue, the silicone oil is V401-90 produced by Shandong Dayi Chemical, and the hydrogen-containing silicone oil is MHQ-4 produced by Shandong Dayi Chemical.
[0015] In one or more embodiments, the non-magnetic conductive particles have a particle size of 1 to 50 μm and a D50 of 8 to 10 μm.
[0016] In one or more embodiments, when curing the conductive adhesive, the curing temperature is first increased from room temperature to 95-105°C within 25-28 seconds, maintained at 95-105°C for 8-12 seconds, then increased to 145-155°C within 8-10 seconds, maintained at 145-155°C for 13-16 seconds, and finally decreased to room temperature within 55-65 seconds.
[0017] In one or more embodiments, the substrate further includes an insulating film disposed on the back side of the base material layer, the insulating film has a thickness of 0.05 to 0.1 mm, and the insulating film is removed after the conductive glue in the conductive through hole is completely cured.
[0018] In one or more embodiments, filter paper is provided between the air guide holes of the air guide plate and the conductive through holes of the substrate, the thickness of the filter paper is 0.02-0.04 mm, and the aperture of the air permeable holes on the filter paper is 0.4-0.5 μm.
[0019] Compared with the prior art, the method for preparing anisotropic conductive adhesive connection sockets for chip testing provided by the present invention achieves uniform filling of conductive adhesive by optimizing the printing process and vacuum negative pressure control, thereby ensuring the conductive performance and signal transmission stability of the chip connection socket, and can significantly reduce the dependence on complex magnetic forming equipment, thereby reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 is a schematic diagram of the layer structure of a substrate in one embodiment of the present invention;
[0022] Figure 2 is a schematic diagram of the three-dimensional structure of a substrate in one embodiment of the present invention;
[0023] Figure 3 is a vacuum pressure curve diagram of the negative pressure generator in Example 1 of the present invention;
[0024] Figure 4 is a pressure curve diagram of the scraper in Example 1 of the present invention;
[0025] Figure 5 is a particle size distribution diagram of silver particles in Example 1 of the present invention;
[0026] Figure 6 is a curing temperature curve diagram of the conductive adhesive in Example 1 of the present invention;
[0027] Figure 7 This is an X-ray scanning result diagram of the sample prepared in Example 1 of the present invention;
[0028] Figure 8 This is a graph showing the FSR parameter test results of the sample prepared in Example 1 of the present invention;
[0029] Fig. 9 This is a diagram showing the insertion loss test results of the sample prepared in Example 1 of the present invention;
[0030] Fig.10 This is a graph showing the return loss test results of the sample prepared in Example 1 of the present invention;
[0031] Fig.11 It is a vacuum pressure curve diagram of the negative pressure generator in Comparative Example 1 of the present invention;
[0032] Fig.12 This is an X-ray scanning result diagram of the sample prepared in Comparative Example 1 of the present invention;
[0033] Fig.13 is a pressure curve diagram of the scraper in Example 2 of the present invention;
[0034] Fig.14 This is an X-ray scanning result diagram of the sample prepared in Comparative Example 2 of the present invention;
[0035] Fig.15 The curing temperature curve of the conductive adhesive in Comparative Example 3 of the present invention is
[0036] Fig.16 This is an X-ray scanning result diagram of the sample prepared in Comparative Example 3 of the present invention;
[0037] Fig.17 This is an X-ray scanning result diagram of the sample prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0039] It should be noted that in the following description, the "parts" representing the amount are weight-based unless otherwise specified. Unless otherwise specified, all numbers used in this specification and claims to represent characteristic dimensions, quantities and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges represented by endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.2, 1.4, 1.55, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0040] In the semiconductor industry, in order to conduct precise chip performance testing, the connector sockets need to be accurately connected to the numerous tiny pins on the chip. The key component of these connector sockets is the conductive channels inside them, which ensure that the signals are correctly transmitted from the test equipment to the pins of the chip. The current mainstream method of making these conductive channels relies on specific magnetic forming equipment, which uses magnetic field force to inject a silicone mixture containing metal particles into the connector socket mold, and uses the magnetic field to guide the metal particles to form a conductive path. This process is based on the principle that metal particles will be redistributed along a specific path under the action of a magnetic field.
[0041] However, with the rapid development of semiconductor technology, traditional connection socket preparation methods, especially those relying on specific magnetic forming equipment, have gradually exposed their shortcomings such as high cost, complex operation and limited adaptability.
[0042] The inventors also found in the process of in-depth research and actual operation that although the magnetic forming equipment can control the distribution path of metal particles to a certain extent and form the expected conductive channel, due to the complexity of the physical properties of the mixture of metal particles and organic silica gel, it is still impossible to completely avoid the random dispersion of metal particles in the organic silica gel. This uncontrollable dispersion phenomenon may cause unexpected electrical connections between conductive channels, that is, short circuits, which directly affects the reliability of the connection socket and the accuracy of the test results.
[0043] Although metal particles will be redistributed under the action of magnetic field force, it is impossible to completely avoid the arbitrary dispersion of metal particles in organic silica gel. This uncontrollable distribution may cause short circuit during testing and affect the accuracy of test results.
[0044] The fundamental reason for this problem is that the distribution of metal particles in organic silicone cannot be completely uniform and controllable. Considering the basic physical properties of magnetic materials, such as magnetization and magnetic susceptibility; the force of the magnetic field on metal particles and the fluidity of particles in the organic silicone medium. In the actual production process, due to the viscosity of organic silicone and the difference in the mass and magnetism of metal particles, it is difficult for metal particles to be completely redistributed according to the magnetic lines under the action of the magnetic field during actual operation, that is, the metal particles cannot move and arrange completely according to the theoretical path.
[0045] Based on an in-depth analysis of the prior art, the present invention proposes an innovative method for preparing anisotropic conductive adhesive connection sockets for chip testing, aiming to overcome the above technical defects. The inventors have comprehensively analyzed the deficiencies of the existing process and realized the limitations of traditional technology in terms of material dependence, process complexity and cost control. In order to solve these problems, the present invention has constructed a new preparation idea, abandoning the reliance on magnetic forming and instead adopting a method combining printing technology with negative pressure technology to achieve efficient and uniform filling of conductive adhesive in the connection socket.
[0046] The core of this technical implementation idea is to achieve uniform filling of conductive glue by optimizing the printing process and vacuum negative pressure control, thereby ensuring the conductivity and signal transmission stability of the chip connection socket. The present invention can significantly reduce the dependence on complex magnetic forming equipment, thereby reducing production costs. At the same time, it can effectively avoid the short circuit problem caused by the random dispersion of metal particles in traditional technologies, thereby ensuring the performance and reliability of the connection socket.
[0047] In one embodiment of the present invention, a method for preparing an anisotropic conductive adhesive connection socket for chip testing specifically comprises the following steps:
[0048] S101: providing a substrate having a plurality of conductive through holes corresponding to pins of a chip to be tested, wherein the substrate comprises a stacked base material layer and an insulating elastic layer.
[0049] It should be noted that the design and manufacture of the substrate must first consider the precise matching with the chip pins. The position and size of each conductive through hole precisely correspond to the pins of the chip to be tested to ensure that during the test, each pin of the chip can be accurately connected to the conductive channel in the connection socket. This precise matching not only helps to improve the accuracy of signal transmission, but also reduces the electrical interference that may occur during the test.
[0050] The structure of the substrate can be composed of a laminated substrate layer and an insulating elastic layer. The substrate layer provides mechanical support and overall stability for the substrate, and can be made of materials such as FR4 (glass fiber reinforced epoxy resin) or other high-strength, high-temperature resistant materials. These materials can not only withstand the mechanical stress that may occur during the test, but also ensure that the shape and size of the conductive vias remain stable throughout the manufacturing and use process.
[0051] The insulating elastic layer can ensure electrical isolation between the various conductive vias, preventing short circuits or signal interference between different channels. In addition, the insulating elastic layer provides a certain degree of flexibility, allowing the conductive vias to adapt to the slight displacement of the chip pins when pressure is applied, ensuring good electrical contact. This design can reduce test errors caused by poor contact and effectively protect the chip pins from mechanical damage.
[0052] The substrate can be manufactured using a variety of techniques, such as laser drilling or chemical etching processes to accurately process the size and location of the conductive vias. These techniques can ensure smooth edges of the vias, reduce resistance and reflection during signal transmission, and further improve the accuracy and stability of the test. For example, in practical applications, an insulating elastic layer can be covered on a substrate layer through a lamination process, and then conductive vias can be processed on the substrate using laser drilling technology.
[0053] In an exemplary embodiment, please refer to Figure 2 As shown, the substrate 20 includes a base layer 21, an adhesive layer 22, an insulating elastic layer 23 and a protective layer 24. The base layer 21 has a first surface and a second surface opposite to each other. The adhesive layer 22, the insulating elastic layer 23 and the protective layer 24 are sequentially stacked on the first surface of the base layer 21.
[0054] The substrate layer 21 is the core support layer of the substrate 20, providing mechanical strength and stability of the entire substrate 20. It can be made of a high-strength, low-expansion coefficient material, such as epoxy resin board (FR4), polyimide or ceramic, etc. The substrate layer 21 has a first surface and a second surface opposite to each other, wherein the first surface is used to be laminated with other layers such as an adhesive layer 22, an insulating elastic layer 23 and a protective layer 24.
[0055] The adhesive layer 22 is located on the first surface of the substrate layer 21, and its main function is to ensure a firm connection between the insulating elastic layer 23 and the substrate layer 21. The adhesive layer 22 is usually made of a material with good adhesion, such as an adhesive film or a double-sided tape, which can provide sufficient adhesion and withstand the temperature changes that may occur during the test process to maintain stable adhesion performance.
[0056] The insulating elastic layer 23 is an electrical isolation layer located on the adhesive layer 22. It is made of a material with certain elasticity and excellent insulation, such as a silicone sheet. The main function of this layer is to provide sufficient elasticity to adapt to the slight position difference of the pins when the connection socket contacts the component under test, ensuring good contact performance, while maintaining excellent electrical insulation to prevent leakage or short circuit of the test signal.
[0057] The protective layer 24 is the outermost layer covering the insulating elastic layer 23, and is mainly composed of a wear-resistant and chemical-resistant material, such as a polyimide film. The protective layer 24 protects the insulating elastic layer 23 below from mechanical damage or chemical corrosion, prolongs the service life of the connection socket, and also provides a certain aesthetic appearance for the connection socket. The protective layer 24 can be treated with anti-static and anti-sticking treatment to avoid sticking during use; it can be treated with hydrophobic treatment to prevent condensation in a low-temperature environment, which affects the test results.
[0058] S102: placing the substrate on an air guide plate of a printing device, so that the air guide holes on the air guide plate are aligned with the conductive through holes on the substrate.
[0059] It should be noted that the alignment between the air guide holes of the air guide plate and the conductive through holes of the substrate directly affects the filling effect of the conductive glue. If the alignment is not accurate, the conductive glue may not be evenly filled into the through holes, resulting in unstable conductivity of the connection socket, and even poor conductivity. Therefore, accurate alignment is the basis for ensuring the smooth progress of subsequent steps.
[0060] To achieve this precise alignment, a high-precision mechanical positioning system or optical alignment technology can be used. For example, the printing equipment can be equipped with an automatic alignment system that detects the position deviation of the substrate and the air guide plate through visual recognition and laser positioning technology, and automatically adjusts it. These systems can control the alignment error at the micron level, thereby ensuring perfect alignment of the conductive vias and the air holes.
[0061] In an exemplary embodiment, filter paper is provided between the air guide holes of the air guide plate and the conductive through holes of the substrate, the thickness of the filter paper is 0.02-0.04 mm, and the aperture of the air holes on the filter paper is 0.4-0.5 μm. During the process of negative pressure-assisted conductive glue filling the conductive through holes, the filter paper can ensure that the conductive glue is filled into the conductive through holes and prevent it from being accidentally sucked into the air guide holes.
[0062] The air guide holes of the air guide plate are responsible for providing negative pressure to suck the conductive glue from the stencil through the conductive through-holes of the substrate. However, under the action of negative pressure, the conductive glue will not only fill the through-holes, but may also be mistakenly sucked into the air guide holes of the air guide plate if the suction force is too large. This misabsorption will cause two problems: first, the conductive glue may not be evenly filled into the conductive through-holes of the substrate, and second, the conductive glue may cause blockage or damage to the equipment after entering the negative pressure system. In order to solve this problem, filter paper is introduced. The filter paper material can be microporous paper with a specific pore size or other suitable filter material (such as PDMS film) with sufficient strength and chemical resistance to resist the chemical properties of the conductive glue.
[0063] The thickness of the filter paper is 0.02-0.04 mm, covering between the first air hole and the conductive through hole of the substrate. The filter paper of moderate thickness will not affect the transmission of negative pressure while maintaining sufficient mechanical strength, ensuring that the negative pressure can effectively act on the conductive glue. In addition, the pore size of the air permeable holes on the filter paper is 0.4-0.5 μm. This tiny pore size makes the filter paper have good air permeability, allowing air or gas to pass smoothly while blocking conductive glue particles. The filter paper plays a dual role: on the one hand, it allows negative pressure to pass through, maintaining the continuity and effectiveness of the conductive glue filling process; on the other hand, it acts as a barrier to prevent the conductive glue from being sucked into the negative pressure system.
[0064] The specific method to achieve this design includes pre-attaching filter paper on the air guide plate to ensure that the size and position of the filter paper are precisely aligned with the first air hole and the conductive through hole of the substrate. For example, a high-precision film laminating machine can be used to accurately attach the filter paper to the air guide plate, and the filter paper can be fixed by vacuum adsorption or mechanical pressing to ensure that it will not shift or fall off during operation.
[0065] S103: Align the vacuum support carrier and the stencil of the printing equipment in the up and down directions, move the air guide plate carrying the substrate between the vacuum support carrier and the stencil, align the air guide holes on the air guide plate with the air suction holes of the vacuum support carrier, and align the conductive through holes of the substrate with the mesh holes of the stencil.
[0066] The moving process can use automated conveying devices that can monitor the position of the air guide plate in real time through sensors and control systems, and make fine adjustments as needed. For example, in a high-precision manufacturing environment, a servo motor-driven conveying system can be used, which uses a feedback mechanism to ensure that every movement of the air guide plate is accurate. In this way, the air guide holes on the air guide plate and the air suction holes of the vacuum support carrier can be seamlessly connected to form a complete airflow channel.
[0067] The stencil can be a metal or polymer plate with high-precision openings, whose opening size and position correspond to the conductive through-holes of the substrate. Through alignment, it is ensured that the conductive glue can smoothly pass through the holes of the stencil into the through-holes of the substrate without deviation or overflow.
[0068] S104: The vacuum support carrier is bonded to the lower surface of the air guide plate, and the stencil is bonded to the upper surface of the substrate.
[0069] In this step, it is necessary to ensure that the vacuum support carrier is tightly fitted to the lower surface of the air guide plate. The vacuum support carrier is usually designed as a smooth plane with good sealing performance. Its function is to firmly fix the air guide plate on it through negative pressure. The bonding process requires that there is no gap between the air guide plate and the vacuum support carrier to prevent negative pressure leakage. Such a tight fit can ensure that in the subsequent printing process, the negative pressure can be effectively transmitted to the conductive through-holes of the substrate, helping the conductive glue to fill smoothly.
[0070] The stencil is the medium through which the conductive glue passes during the printing process. Its aperture (about 80% of the aperture of the conductive through hole) and position correspond to the conductive through holes of the substrate. During the printing process, the stencil needs to fit tightly to the surface of the substrate to ensure that the conductive glue can be evenly distributed through the holes of the stencil into the conductive through holes of the substrate.
[0071] S105: The vacuum support carrier is connected to the negative pressure generator to form negative pressure in the conductive through hole through the air suction hole and the air guide hole.
[0072] When the vacuum support carrier is connected to the negative pressure generator, the negative pressure is transmitted to the air guide holes on the air guide plate through the air suction holes, and then directly acts on the conductive through holes of the substrate through these air holes. The formation of negative pressure creates a downward suction force inside the through hole, which helps the conductive glue to be pulled into the conductive through hole during the printing process, thereby achieving more uniform and sufficient filling.
[0073] S106: Apply the conductive glue on the screen, and use a scraper to print back and forth 24 to 30 times, so that the conductive glue is filled into the conductive through-hole under the pressure of the scraper and the negative pressure; during the printing process, the vacuum pressure of the negative pressure generator first gradually increases to a first pressure, and after maintaining the first pressure for a predetermined time, gradually increases to a second pressure, and maintains the second pressure until the printing is completed; the scraper maintains the first pressure during the first 6 to 8 printings, the scraper maintains the second pressure during the middle 8 to 10 printings, and the scraper maintains the third pressure during the last 10 to 12 printings, and the first pressure>the second pressure>the third pressure.
[0074] The conductive glue is evenly coated on the stencil, and the conductive glue is filled into the conductive through-holes of the substrate layer by layer under the dual effects of pressure and negative pressure through the reciprocating printing of the scraper. In order to ensure the accuracy and uniformity of the conductive glue filling, this process adopts multiple printings, and the filling effect is optimized by gradually adjusting the scraper pressure and negative pressure.
[0075] Use a scraper to perform 24 to 30 reciprocating prints. During this process, the scraper presses the conductive glue from the holes of the stencil into the conductive through-holes of the substrate at a set pressure. The number of printings is set to ensure that the conductive glue can be filled layer by layer to avoid overflow or unevenness caused by excessive filling at one time. Through multiple printings, the conductive glue gradually fills the through-holes under the action of pressure, forming a continuous and stable conductive path.
[0076] A key control point in the printing process is the dynamic adjustment of the scraper pressure and negative pressure. In order to achieve the best filling effect, the printing process is divided into three stages: in the first 6 to 8 printings, the scraper maintains a high first pressure, and the negative pressure gradually increases to the first pressure. The purpose of this stage is to quickly press the conductive glue into the through hole with a large pressure, and at the same time use the gradually increasing negative pressure to help the conductive glue overcome the surface tension and quickly fill the bottom of the through hole. This stage effectively ensures the initial filling of the conductive glue.
[0077] During the 8-10 printings in the middle, the scraper pressure is reduced to the second pressure, and the negative pressure is maintained at the first pressure. The focus of this stage is to optimize the distribution of the conductive glue so that it can be filled more evenly in the through-hole. The lower scraper pressure prevents excessive conductive glue accumulation, while the stable negative pressure helps to further eliminate the bubbles that may remain in the through-hole and ensure the tightness of the filling.
[0078] For the last 10 to 12 prints, the scraper maintains the lowest third pressure, while the negative pressure is maintained at the first pressure and then gradually increased to the second pressure, and maintained at the second pressure. The main purpose of this stage is to level the surface of the conductive adhesive, ensure that the filler is flush with the substrate surface, and prepare for the subsequent curing process. By reducing the pressure, excessive pressure accumulation in the through hole can be avoided, preventing the conductive adhesive from overflowing the through hole or causing surface unevenness.
[0079] In an exemplary embodiment, the time for a single printing of the scraper is 8 to 10 seconds, and the displacement of a single printing is 180 to 200 mm. The time for a single printing of the scraper refers to the time required for the scraper to move from one side of the printing area to the other side. The time range set to 8 to 10 seconds means that the speed of movement of the scraper on the stencil needs to be moderate. This time setting is to ensure uniform distribution of the conductive glue while avoiding colloid accumulation due to excessive speed or excessive diffusion of the colloid due to too slow speed. If the scraper moves too fast, the conductive glue may not be able to fully enter the conductive through-holes of the substrate, resulting in uneven filling; if the moving speed is too slow, it may cause the conductive glue to accumulate outside the through-hole, affecting the final conductive path quality. Therefore, the time setting of 8 to 10 seconds provides a balanced operating window for the entire printing process, which helps to ensure effective filling of the conductive glue.
[0080] The displacement of a single print is the distance covered by the scraper in one printing movement, which is 180 to 200 mm. The setting of this displacement directly affects the pressure distribution of the scraper on the stencil and the flow direction of the conductive adhesive. In actual operation, this displacement is matched with the size of the stencil and substrate to ensure that the entire printing area can be completely covered in one scraper operation. By controlling the displacement, it can be ensured that the conductive adhesive passes evenly through the openings of the stencil and forms a smooth and continuous filling layer in the conductive through-holes of the substrate. If the displacement is insufficient, the conductive adhesive may not be fully filled in some areas; if the displacement is too large, the scraper pressure may be uneven, affecting the uniformity of the conductive adhesive.
[0081] In an exemplary embodiment, during the printing process, the vacuum pressure of the negative pressure generator gradually increases to 0.06-0.08 MPa within 48-60 seconds, maintains at 0.06-0.08 MPa for 112-140 seconds, and then gradually increases to 0.09-0.11 MPa within 24-30 seconds, and maintains at 0.09-0.11 MPa until printing is completed.
[0082] At the beginning of the printing process, the negative pressure generator gradually increases the vacuum pressure to 0.06 to 0.08 MPa within 48 to 60 seconds. The purpose of the gradual pressurization at this stage is to create an appropriate negative pressure environment for the initial filling of the conductive glue. By slowly increasing the negative pressure, it is possible to prevent the conductive glue from generating eddy currents or uneven distribution due to excessive pressure when entering the through-hole. At the same time, the moderate initial negative pressure helps the conductive glue overcome surface tension, making it easier to enter the tiny conductive through-holes and avoid the formation of bubbles or voids in the through-holes.
[0083] Next, after reaching a vacuum pressure of 0.06 to 0.08 MPa, the negative pressure is maintained constant for 112 to 140 seconds. The purpose of this constant pressure stage is to stabilize the flow of the conductive adhesive in the through-hole so that it gradually fills the entire through-hole space. In this process, maintaining a constant negative pressure ensures that the conductive adhesive can fully diffuse and fill each through-hole, reducing the risk of uneven filling. This stage is a key step to ensure that the conductive adhesive fully enters the through-hole and eliminates bubbles.
[0084] After that, the negative pressure generator further increases the vacuum pressure to 0.09 to 0.11 MPa within 24 to 30 seconds, and maintains this higher pressure until printing is completed. The purpose of this process is to thoroughly compact the conductive glue through a higher negative pressure so that it forms a tight conductive path in the through-hole. The high pressure at this stage ensures that all gaps in the conductive glue in the through-hole are filled, and residual bubbles or impurities are eliminated, thereby improving the density and conductivity of the conductive glue in the conductive through-hole. The final high-pressure stage also helps the conductive glue reach an optimal filling state before curing, preparing for the subsequent thermal curing step.
[0085] The specific way to achieve this process can be accomplished through printing equipment equipped with an adjustable vacuum system. These systems usually contain precision pressure sensors and controllers that can gradually adjust the vacuum pressure according to a preset program. For example, in a semiconductor manufacturing environment, a PLC (programmable logic controller) can be used to control the operation of the negative pressure generator, and the vacuum pressure can be monitored and adjusted in real time to ensure that the pressure changes at each stage meet the process requirements.
[0086] In an exemplary embodiment, the pressure of the scraper is 55-65N during the first 6-8 printings, 35-45N during the middle 8-10 printings, and 25-35N during the last 10-12 printings.
[0087] During the first 6 to 8 printings, the pressure of the scraper is set at 55-65N. This higher initial pressure helps to quickly press the conductive glue from the holes of the stencil into the conductive through-holes of the substrate. In the early stage of printing, since the through-holes are not fully filled, the higher pressure can overcome the viscosity of the conductive glue, ensure that the glue enters the bottom of the through-holes and initially fills the entire through-hole space. High-pressure printing at this stage helps to establish a base layer of conductive glue, form a preliminary conductive path, and lay the foundation for subsequent filling.
[0088] During the middle 8 to 10 printings, the scraper pressure is reduced to 35-45N. This medium pressure setting is to optimize the distribution of the conductive glue so that it can be filled more evenly in the conductive through-hole. At this stage, the initial filling of the conductive glue has covered most of the through-hole area, but it still needs to be further evenly distributed. The medium pressure can reduce the flow resistance of the conductive glue in the through-hole, prevent excessive colloid from accumulating in certain areas, and help to expel the air or bubbles that may remain in the through-hole, ensuring the uniformity and stability of the filling.
[0089] Finally, during the last 10 to 12 prints, the scraper pressure is further reduced to 25 to 35N. This lower pressure setting is intended to smooth the surface of the conductive glue and ensure that the conductive glue is ideally filled in the through-hole. At this stage, the conductive glue has been basically filled, and the lower pressure helps to fine-tune the distribution of the conductive glue and avoid overflow caused by excessive pressure. At the same time, the lower pressure can also prevent excessive compression of the conductive glue and maintain the uniformity of the filling in the through-hole, thereby forming a smooth and continuous conductive path.
[0090] This staged pressure control can maximize the uniform distribution and bubble-free filling of the conductive adhesive throughout the through-hole, thereby improving the stability of the conductive path and the conductive performance.
[0091] The specific way to achieve this process can be accomplished through automated printing equipment, which is equipped with a sophisticated pressure control system that can gradually adjust the scraper pressure according to the set program. For example, in some high-precision semiconductor manufacturing equipment, the scraper pressure adjustment is controlled by a servo motor and a force sensor to ensure that the pressure of each print can accurately meet the preset requirements. This automated control not only improves the accuracy of printing, but also reduces the error of manual operation and ensures the consistency of each batch of products.
[0092] In an exemplary embodiment, the raw material composition of the conductive adhesive includes the following raw materials, calculated by mass: 80-90 parts of silicone resin with a molecular weight of 30-50, 10-20 parts of silicone oil, 0.5-1 part of inhibitor, 5-10 parts of hydrogenated silicone oil, 0.5-1 part of platinum catalyst, and 500-700 parts of non-magnetic conductive particles.
[0093] The silicone resin with a molecular weight of 30 to 50 accounts for 80 to 90 parts. This is the base material of the conductive adhesive and mainly provides adhesion and mechanical strength. The medium molecular weight silicone resin has good flexibility and weather resistance, and can maintain the stability and toughness of the conductive adhesive after curing. This resin has a moderate molecular weight, which can provide sufficient strength without being too rigid. It is suitable for forming a stable conductive channel in a tiny conductive through hole, and the moderate viscosity is conducive to filling the conductive through hole. The silicone resin is preferably HSV-1510 from Jiangxi Riyue.
[0094] The silicone oil accounts for 10 to 20 parts, and its main function is to adjust the viscosity and fluidity of the conductive adhesive. By adding an appropriate amount of silicone oil, the conductive adhesive can flow more easily during the printing and filling process, ensuring that it can be smoothly filled into the conductive through-hole. This fluidity adjustment helps to achieve uniform filling and avoid the generation of bubbles. In addition, the silicone oil can also improve the flexibility of the conductive adhesive after curing and enhance its anti-fatigue performance. The silicone oil is preferably V401-90 from Shandong Dayi Chemical.
[0095] The inhibitor is added in an amount of 0.5 to 1 part, which is a key component used to control the curing speed of the conductive adhesive. The role of the inhibitor is to delay the action time of the platinum catalyst, thereby preventing the conductive adhesive from curing prematurely during operation and ensuring sufficient operating time to complete the filling and printing process. By controlling the amount of inhibitor, the operating window of the conductive adhesive can be adjusted according to the process requirements to ensure the stability of the production process.
[0096] The amount of hydrogen-containing silicone oil added is 5 to 10 parts. This component is an important substance involved in the cross-linking reaction. During the curing process, the hydrogen-containing silicone oil reacts with the vinyl group in the silicone resin to form a cross-linking structure, which eventually transforms the conductive adhesive from a liquid or semi-liquid state to a solid state. The proportion of hydrogen-containing silicone oil directly affects the curing speed and final hardness of the conductive adhesive. By controlling its dosage, the curing characteristics of the conductive adhesive can be adjusted to meet the needs of different use environments. The hydrogen-containing silicone oil is preferably MHQ-4 from Shandong Dayi Chemical.
[0097] The amount of platinum catalyst added is 0.5 to 1 part. Platinum catalyst is the core catalyst of the entire curing reaction. It can greatly accelerate the addition reaction between hydrogen-containing silicone oil and silicone resin, thereby improving the curing efficiency. The amount of platinum catalyst needs to be precisely controlled. Too much may cause too fast reaction and affect the filling process of the conductive adhesive; too little may cause incomplete curing and affect the mechanical strength and conductive properties of the final product.
[0098] The amount of non-magnetic conductive particles added is 500 to 700 parts. This is the conductive filler of the conductive glue, which is responsible for forming a conductive path in the colloid after curing. The high conductivity and moderate particle size of the non-magnetic conductive particles ensure that the conductive glue has excellent conductive properties after curing. By controlling the amount of non-magnetic conductive particles added, the overall conductivity and impedance characteristics of the conductive glue can be adjusted to meet the needs of different chip tests. The non-magnetic conductive particles are preferably silver or copper particles.
[0099] The inventors found that when ferromagnetic particles such as silver nickel and gold nickel are used as conductive particles in the conductive adhesive, the filling effect of the conductive adhesive in the conductive through hole is not good. The reason may be that when magnetic conductive particles such as gold nickel particles and silver nickel particles rub against each other during the filling process, the friction force will generate a tiny magnetic field on the surface of these particles. This phenomenon is called the friction magnetization effect. Although the magnetism of these magnetic particles themselves may be weak, the magnetic field will be further enhanced during the friction process due to the relative movement between the particles. This locally enhanced magnetic field has a direct impact on the rheological properties of the conductive adhesive.
[0100] The conductive adhesive in the present invention is a complex multiphase system, including a matrix (such as silicone resin), a conductive filler (such as conductive particles) and other functional additives. The viscosity of the conductive adhesive is an important parameter of its fluidity, which directly affects its filling effect in the conductive through-hole. When the magnetic field generated by the magnetic particles acts on the conductive adhesive, the magnetic particles inside the conductive adhesive will be affected by the magnetic force, causing their motion trajectory to change. This magnetic effect may cause mutual attraction or repulsion between particles, thereby affecting the overall fluidity of the conductive adhesive.
[0101] Specifically, magnetic conductive particles may form chain or cluster structures in the conductive adhesive under the action of a magnetic field. This structure will significantly increase the viscosity of the conductive adhesive, causing its fluidity to decrease, and thus it will not be able to smoothly enter the tiny gaps of the conductive through-holes during the filling process. In addition, the directional arrangement of magnetic particles may also cause the flow path of the conductive adhesive to be uneven, further reducing the uniformity of filling.
[0102] The aggregation effect of magnetic conductive particles in the conductive adhesive is also an important factor affecting the filling effect. Under the action of the magnetic field, the mutual attraction between the particles may cause them to form aggregates in the conductive adhesive. These aggregates, due to their large size, may block the conductive vias, resulting in incomplete local filling or the formation of bubbles. This phenomenon not only reduces the filling efficiency of the conductive adhesive, but also may cause discontinuity of the conductive path within the conductive vias, thereby affecting the final conductive performance.
[0103] In addition, the magnetic particle aggregates formed in the conductive adhesive may further affect the uniformity of the conductive path during the curing process. Due to the uneven distribution of these aggregates, the conductive path in the conductive through hole after the conductive adhesive is cured may have uneven conductivity, resulting in reduced stability of signal transmission.
[0104] In an exemplary embodiment, the particle size of the non-magnetic conductive particles is 1 to 50 μm and the D50 is 8 to 10 μm. The particle size range of 1 to 50 μm means that the size of the non-magnetic conductive particles in the conductive adhesive ranges from a tiny 1 μm to a relatively large 50 μm. This wide particle size distribution allows the particles to form a dense filling structure in the conductive adhesive, thereby increasing the density and continuity of the conductive path. Smaller particles (1 to 10 μm) can fill smaller gaps in the conductive through-holes of the substrate, ensuring that the conductive adhesive forms a dense and uniform conductive network after curing. Larger particles (20 to 50 μm) help form a skeleton structure in the conductive adhesive, provide a stable conductive channel and enhance the mechanical strength of the conductive adhesive.
[0105] The D50 value of 8-10μm is a statistical parameter describing the particle size distribution, indicating that 50% of the particles are less than 8-10μm in diameter. The setting of the D50 value reflects the main particle size distribution of the particles in the conductive adhesive. The particle size within this range has an impact on the performance of the conductive adhesive. The D50 value of 8-10μm can reduce the voids and bubbles that may appear during the filling process and enhance the mechanical strength and stability of the conductive adhesive.
[0106] The specific way to achieve this particle distribution can be achieved by controlling the manufacturing process of the particles. For example, the manufacture of non-magnetic conductive particles can be done by mechanical grinding or atomization. During the production process, the particle size distribution of the particles can be precisely adjusted by controlling the grinding time, grinding media and atomization parameters. Subsequently, the particles are controlled within the range of 1 to 50 μm through screening and grading techniques, and the D50 value is measured by a particle size analyzer to ensure that the set specifications are met.
[0107] S107: thermally curing the printed substrate filled with the conductive adhesive to cure the conductive adhesive in the conductive through hole, thereby obtaining a chip connection socket.
[0108] The purpose of thermal curing is to make the chemical components of the conductive adhesive react by heating to form a cross-linked structure, and finally transform the conductive adhesive from a liquid or semi-liquid state to a solid state. This curing process not only fixes the conductive adhesive in the conductive through-hole, but also improves its mechanical strength and conductive properties.
[0109] In an exemplary embodiment, when curing the conductive adhesive, the curing temperature is first increased from room temperature to 95-105°C within 25-28 seconds, maintained at 95-105°C for 8-12 seconds, then increased to 145-155°C within 8-10 seconds, maintained at 145-155°C for 13-16 seconds, and finally decreased to room temperature within 55-65 seconds.
[0110] At the beginning of curing, the curing temperature gradually rises from room temperature to 95-105°C within 25-28 seconds. This temperature rise stage is intended to quickly start the chemical reaction inside the conductive adhesive, especially the cross-linking reaction between hydrogenated silicone oil and silicone resin. Within this temperature range, the conductive adhesive begins to gradually change from liquid or semi-liquid to solid, and the internal structure begins to form. The temperature rise rate at this stage is relatively fast, which can effectively reduce the stress concentration inside the colloid and prevent the formation of uneven cross-linking structure in the early stage of curing.
[0111] Then, keep it at 95-105℃ for 8-12s. The purpose of this constant temperature stage is to ensure that the reaction inside the conductive adhesive is fully carried out and a preliminary cross-linking network is formed. At this time, the maintenance of temperature can make the molecular structure of the conductive adhesive uniform and reduce the internal tension unevenness or crack formation caused by too fast heating. This stage is the key to the curing process of the conductive adhesive. By controlling the temperature and time, it can ensure that the conductive adhesive has good mechanical properties and preliminary conductivity.
[0112] Next, the temperature is further raised to 145-155°C within 8-10 seconds. The purpose of this heating stage is to accelerate the final curing process of the conductive adhesive and ensure that all chemical reactions are completely carried out. At higher temperatures, the molecular chains in the conductive adhesive are further cross-linked to form a denser and more stable structure. The rapid heating in this stage helps to reduce the curing time while avoiding material degradation or performance degradation that may result from long-term high temperature treatment.
[0113] Maintaining 13 to 16 seconds at 145 to 155°C is the final step of curing, ensuring that the conductive adhesive is fully cured to form a high-strength conductive path. At this stage, the physical and chemical properties of the conductive adhesive tend to be stable, and the conductivity and mechanical properties reach their optimal state. By maintaining this temperature range, the cross-linking density of the conductive adhesive can be maximized, ensuring its reliability and durability in practical applications.
[0114] Finally, the temperature gradually drops to room temperature within 55 to 65 seconds. This slow cooling process can effectively reduce internal stress and prevent cracking or deformation of the material caused by a sudden drop in temperature. By gradually cooling, the internal structure of the conductive adhesive is stabilized, avoiding increased brittleness or reduced conductivity caused by rapid cooling. This cooling process can also ensure that the conductive adhesive has good dimensional stability after curing and will not shrink or expand during subsequent use.
[0115] In an exemplary embodiment, please refer to Figure 1 and Figure 2As shown, the substrate 20 further includes an insulating film 25 disposed on the back of the base material layer 21, and the thickness of the insulating film 25 is 0.05-0.1 mm. After the conductive glue in the conductive through hole 26 is completely cured, the insulating film 25 is removed. The conductive through hole 26 passes through the base material layer 21, the adhesive layer 22, the insulating elastic layer 23, the protective layer 24 and the insulating film 25. The insulating film 25 can be made of a material with high electrical insulation performance, such as a polyimide film or an epoxy resin film.
[0116] Since the conductive vias run through the entire substrate 20 (including the insulating film 25), when the insulating film 25 is removed, the cured conductive adhesive will slightly protrude from the back of the substrate layer 21 to form bumps. These bumps significantly improve the electrical contact of the conductive adhesive during chip testing. Specifically, these bumps can form a more reliable contact with the probes or contact points of the test equipment, thereby reducing contact resistance and improving the stability and accuracy of signal transmission.
[0117] The present invention will be further described below in conjunction with specific embodiments.
[0118] Example 1
[0119] The FR4 board is used as the substrate layer. The thickness of the FR4 board is 0.2mm. The insulating silicone sheet is bonded to the front surface of the FR4 board. The bonding method can be achieved by double-sided high-temperature resistant tape. The glass fiber cloth of the FR4 board is E-glass, which has good electrical properties, water resistance, and thermal stability. At a frequency of 10GHz, the dielectric constant Dk is 6.6, the thermal expansion coefficient is 3.4ppm / ℃, and the dielectric loss factor Df is 0.0066. The intersection of the warp and weft yarns and the aperture design of the board should avoid the "glass fiber effect".
[0120] The single-sided adhesive PI protective film is bonded to the front of the insulating silicone sheet, and the single-sided adhesive insulating film is bonded to the back of the FR4 board. The insulating film has appropriate bonding strength with the FR4 board and the conductive adhesive, and the conductive adhesive is easy to peel off after curing. After bonding, measure the thickness of the substrate to ensure that it is within the design tolerance range.
[0121] Cut the filter paper into a suitable shape, the size of which can just cover the air guide holes of the air guide plate. The filter paper is made of PDMS film, with a thickness of 0.03mm and an air permeability of 0.45μm. Figure 2 In the form shown, the processing of the substrate requires high-precision processing measures to ensure the tolerance of each hole diameter. For example, laser processing must strictly control the diameter-to-depth ratio and processing inclination angle to reduce carbonization of the hole wall.
[0122] Put the substrate upside down on the air guide plate, and fix it with sealing strips around to ensure that the entire plane and the plane of the air guide plate are completely in contact. The air guide plate here is made of rigid, small-deformation material. The surface of the substrate and the surface of the air guide plate are both provided with semi-blind Mark points, and foolproof treatment is done to facilitate the alignment of the screen and the air guide plate. The alignment of the substrate and the air guide plate adopts edge positioning, so the printing environment needs to ensure 25℃, RH40%.
[0123] Before printing, fix the vacuum support carrier to the bottom of the printing equipment. Install and fix the stencil on the upper track of the printing equipment, and use the visual positioning system to position the vacuum support carrier and the stencil. The mark points on the stencil here are processed with through holes, which is convenient for adjusting the position of the stencil and keeping the vacuum support carrier vertical. The stencil uses a 0.15mm thick steel mesh with an anti-stick coating on the lower surface of the steel mesh. The aperture is 0.8d of the substrate aperture, and the holes are symmetrical in four directions to avoid deformation of the stencil as the number of printings increases.
[0124] The conveyor is used to convey the air guide plate with the substrate to between the vacuum support carrier and the printing stencil, so that the air guide holes on the air guide plate are aligned with the air suction holes of the vacuum support carrier, and the conductive through holes of the substrate are aligned with the mesh holes of the stencil. The conveyor here uses a precise positioning fixture and performs foolproof processing to ensure that the holes of the printing fixture are accurately aligned with the holes of the stencil.
[0125] The platform of the fixed vacuum support carrier at the bottom rises to fit the lower surface of the air guide plate, and the printing stencil descends to fit the printing plane of the substrate. During the operation, the bottom platform and the printing stencil should be raised and lowered at the same time, and the height should be strictly controlled to ensure that the stencil is in a horizontal state. The secondary calibration is performed through the visual positioning of the equipment to align the holes of the stencil with the holes of the sample; pay attention to ensure that the mark points of the vacuum carrier, sample, and stencil are consistent.
[0126] The vacuum support carrier is connected to the negative pressure generator, and negative pressure is formed in the conductive through-hole through the air suction hole and the air guide hole. The conductive glue is coated on the screen, and the scraper is used to reciprocate 30 times (15 times in one direction). The single scraper displacement is 200mm, and the single printing time is 10s. The conductive glue is filled into the conductive through-hole under the pressure of the scraper and the negative pressure. During the printing process, the vacuum pressure curve of the negative pressure generator is as follows: Figure 3 As shown, the pressure curve of the scraper is as follows Figure 4 The raw material ratio of the conductive adhesive is: 85 parts of organic silicone resin (HSV-1510, molecular weight is about 32), 15 parts of organic silicone oil (V401-90), 0.7 parts of inhibitor (alkynyl cyclohexanol), 8 parts of hydrogen-containing silicone oil (MHQ-4), 0.8 parts of platinum catalyst (metal platinum), 600 parts of silver particles; the particle size distribution of the silver particles is as follows Figure 5 shown.
[0127] After printing is completed, the bottom platform descends, the screen rises, and the printing jig exits the working area of the printing equipment through the conveyor track. The printing effect is observed. If it is satisfactory, curing is carried out. If it is not satisfactory, the printing steps are repeated. The curing temperature is based on Figure 6 The curve shown is temperature controlled curing.
[0128] After curing, the sample is removed from the air guide plate, the residual glue on both sides is cleaned, and the first surface treatment is performed to remove the insulating film and expose the bumps. The sample is scanned and tested for the filling effect in the hole by X-ray, and the FSR parameters and S parameters are tested. The results of the X-ray hole filling effect scan test are as follows: Figure 7 As shown, the FSR parameter test results are as follows Figure 8 As shown, the S parameter test results are as follows Fig. 9 and Fig.10 shown.
[0129] Comparative Example 1
[0130] Compared with Example 1, the vacuum pressure curve of the negative pressure generator during printing is Fig.11 Except for the above, the other preparation conditions are the same as those in Example 1. The X-ray hole filling effect scanning test results of the sample prepared in Comparative Example 1 are as follows: Fig.12 shown.
[0131] Comparative Example 2
[0132] Compared with Example 1, except that the pressure curve of the scraper during printing adopts Fig.13 Except for the above, the other preparation conditions are the same as those in Example 1. The X-ray hole filling effect scanning test results of the sample prepared in Comparative Example 2 are as follows: Fig.14 shown.
[0133] Comparative Example 3
[0134] Compared with Example 1, the curing temperature curve of the conductive adhesive after printing is adopted Fig.15 Except for the above, the other preparation conditions are the same as those in Example 1. The X-ray hole filling effect scanning test results of the sample prepared in Comparative Example 3 are as follows: Fig.16 shown.
[0135] Comparative Example 4
[0136] Compared with Example 1, except that the organic silicone resin in the conductive adhesive is replaced with an organic silicone resin with a molecular weight of about 70, the other preparation conditions are the same as those of Example 1. The X-ray hole filling effect scanning test results of the sample prepared in Comparative Example 4 are as follows: Fig.17 shown.
[0137] From the above-mentioned embodiments, comparative examples and test results, it can be seen that the samples prepared in the embodiments of the present invention have good filling effect of conductive glue in the conductive through-holes, basically no pores, and good electrical performance. However, the samples prepared in the comparative examples have poor filling effect of conductive glue in the conductive through-holes, have many pores, and cannot smoothly achieve electrical conduction during the electrical test.
[0138] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0139] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing an anisotropic conductive adhesive connection socket for chip testing, characterized in that: include: Providing a substrate having a plurality of conductive through holes corresponding to the pins of the chip to be tested, the substrate comprising a stacked base material layer and an insulating elastic layer; Placing the substrate on an air guide plate of a printing device so that the air guide holes on the air guide plate are aligned with the conductive through holes on the substrate; Align the vacuum support carrier and the stencil of the printing equipment in the vertical direction, move the air guide plate carrying the substrate between the vacuum support carrier and the stencil, align the air guide holes on the air guide plate with the air suction holes of the vacuum support carrier, and align the conductive through holes of the substrate with the mesh holes of the stencil; The vacuum support carrier is fitted to the lower surface of the air guide plate, and the stencil is fitted to the upper surface of the substrate; The vacuum support carrier is connected to the negative pressure generator to form negative pressure in the conductive through hole through the air suction hole and the air guide hole; The conductive glue is coated on the screen, and a scraper is used to reciprocate and print 24 to 30 times, so that the conductive glue is filled into the conductive through hole under the pressure of the scraper and the negative pressure; during the printing process, the vacuum pressure of the negative pressure generator is gradually increased to the first pressure, and after being maintained at the first pressure for a predetermined time, it is gradually increased to the second pressure, and maintained at the second pressure until the printing is completed; the scraper maintains the first pressure during the first 6 to 8 printings, the scraper maintains the second pressure during the middle 8 to 10 printings, and the scraper maintains the third pressure during the last 10 to 12 printings, and the first pressure> the second pressure> the third pressure; The printed substrate filled with the conductive adhesive is thermally cured to solidify the conductive adhesive in the conductive through hole to obtain a chip connection socket.
2. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 1, characterized in that: The single printing time of the scraper is 8 to 10 seconds, and the single printing displacement is 180 to 200 mm.
3. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 2, characterized in that: During the printing process, the vacuum pressure of the negative pressure generator gradually increases to 0.06-0.08 MPa within 48-60 seconds, maintains at 0.06-0.08 MPa for 112-140 seconds, and then gradually increases to 0.09-0.11 MPa within 24-30 seconds, and maintains at 0.09-0.11 MPa until printing is completed.
4. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 2, characterized in that: The pressure of the scraper is 55-65N during the first 6-8 printings, 35-45N during the middle 8-10 printings, and 25-35N during the last 10-12 printings.
5. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 1, characterized in that: The raw material composition of the conductive adhesive includes the following raw materials, calculated by mass: 80-90 parts of organic silicon resin with a molecular weight of 30-50, 10-20 parts of organic silicon oil, 0.5-1 part of inhibitor, 5-10 parts of hydrogen-containing silicone oil, 0.5-1 part of platinum catalyst, and 500-700 parts of non-magnetic conductive particles.
6. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 5, characterized in that: The organic silicone resin is HSV-1510 produced by Jiangxi Riyue, the organic silicone oil is V401-90 produced by Shandong Dayi Chemical, and the hydrogen-containing silicone oil is MHQ-4 produced by Shandong Dayi Chemical.
7. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 5, characterized in that: The non-magnetic conductive particles have a particle size of 1 to 50 μm and a D50 of 8 to 10 μm.
8. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 5, characterized in that: When curing the conductive adhesive, the curing temperature is first increased from room temperature to 95-105° C. within 25-28 seconds, maintained at 95-105° C. for 8-12 seconds, then increased to 145-155° C. within 8-10 seconds, maintained at 145-155° C. for 13-16 seconds, and finally decreased to room temperature within 55-65 seconds.
9. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 1, characterized in that: The substrate further comprises an insulating film disposed on the back side of the base material layer, the thickness of the insulating film is 0.05-0.1 mm, and the insulating film is removed after the conductive glue in the conductive through hole is completely cured.
10. The method for preparing anisotropic conductive adhesive connection socket for chip testing according to claim 1, characterized in that: Filter paper is arranged between the air guide holes of the air guide plate and the conductive through holes of the substrate. The thickness of the filter paper is 0.02-0.04 mm, and the aperture of the air permeable holes on the filter paper is 0.4-0.5 μm.
Citation Information
Patent Citations
Slurry vacuum hole plugging device and hole plugging method
CN113225922A
Printed-circuit board and method of manufacturing same
JP2005093556A